Pragtvognen fra Fredbjerg - Schovsbo, Per Ole (Kuml, 2007)
New investigations of the magnificent cart from Fredbjerg The magnificent carts of Dejbjerg type from the Pre-Roman Iron Age (fig. 6) appear to be related to the vehicles used by the elite in the Celtic oppidae in Late la Tène times. The Danish group of carts comprises six almost identical vehicles (fig. 3), presumably produced in Danish workshops during Martens’ phase IIB 2. Of these, two were deposited in graves (those from Langå and Kraghede) in phase IIB 2, two were abandoned on settlements in the Early Roman Iron Age and the final two were deposited in the bog at Dejbjerg, possibly late in the Early Roman Iron Age, as more than 100 year old antiquities. The Danish carts each included more than 300 metal fitting of iron or bronze, a similar number of nails and more than 100 wooden components. A replica was constructed using methods as near as possible to the original in collaboration between Odense Museums and the Iron Age Village of Næsby in 1983-88. The vehicle was built according to drawings and descriptions produced on the basis of investigations of the all the Danish examples. The project was then continued by the museum in Skjern-Egvad in 1996-2002. It has given such extensive knowledge of the cart’s construction and its performance that it is now possible to interpret wear traces and repairs on the original cart components. In 1969, potsherds, quernstones and bronze fittings turned up on a newly ploughed moorland plot at Fredbjerg in Western Himmerland (fig. 1). The items were declared to be danefæ, i.e. treasure trove belonging to the Danish State, by the Keeper of National Antiquities and their discovery prompted the Prehistoric Museum at Moesgård to carry out an archaeological excavation. This revealed the remains of a longhouse with living quarters to the west and a sunken eastern end (fig. 2) in which the remains of a cart of Dejbjerg type were found (figs. 4-8). North of the house – not far from the original find site for the bronze fittings, which probably derive from an ornamented yoke – were traces of smithing and bronze casting activities (figs. 11-12). The remains of the yoke and cart formed part of the metal depot from a workshop associated with the last phase of the house. This was dated on the basis of pottery to the first half of the Early Roman Iron Age. At least two further houses were located in the area but it is uncertain whether there was a village at the site. The best parallel to this find is seen in the cart fittings from the longhouse in the village at Dankirke, which burnt down in the first part of the Early Roman Iron Age. In addition to a number of iron fittings (figs. 4, 5, 8) the cart remains from Fredbjerg comprise parts of the undercarriage and the body of the vehicle; these are of Dejbjerg I type. The boards of the undercarriage had fingered fittings with rectangular perforations (fig. 5). The very long axle bolts on the shafts indicate a heavy axle construction (fig. 4). A very long iron fitting probably derives from the cart’s front axle. The corner plates from the body of the vehicle were found together with an iron-reinforced handle (fig. 6). Fluted ornamental nails (fig. 7) show no evidence of the red enamel seen on corresponding nails from Dejbjerg II. In addition to above, there are the cast fittings for a pikestaff or goad (stimulus) (fig. 10) and two cast ring-headed pins of bronze (fig. 9); these presumably constitute parts of the harness. The remaining bronzes comprise animal figures, rods and punch-decorated sheet fittings (figs. 11-12) which probably plated a wooden yoke. There are no exact parallels to a yoke of this type but a number of leather decorated yokes from chariot burials dated to the Hallstatt period show a certain similarity to the punch-decorated fittings from Fredbjerg (fig. 13). The double ducks may have functioned as terrets (rein rings) on the yoke. The Fredbjerg cart has, therefore, both fittings and ornamentation in common with the other carts of Dejbjerg I type, as well as having a series of special, local features. This suggests that some of the cart’s cast and punch-decorated bronze fittings could have been based on the same models as the fittings seen on the other carts, whereas the other fittings may have been produced according to local models related to the zoomorphic ornaments such as fibulae, Holstein belts and North Jutish cast belts. Jens Martens links these to the first horizon of princely graves in his phase IIB 1 (fig. 15). As the Fredbjerg house was constructed in Martens’ phase IIB 2, and abandoned in the first part of the Early Roman Iron Age, the cart is slightly older than the house. The Fredbjerg cart was – like the other examples – produced in one or more Danish workshops by Celtic influenced craftsmen as a symbol demonstrating the power of the weapon-bearing elite, described by Tacitus in Germania (chapter 10) from 98 BC – perhaps on the basis of an older tradition. Shortly after the birth of Christ the elite came under the influence of Roman culture (and mythology) and the carts were broken up. Only a few were preserved and these apparently functioned in rites of the fertility cult (without weapons) associated with the cart cleansing ceremony which Tacitus describes in the above-mentioned work (chapter 40), probably according to a later tradition. If it is true that Nerthus (Njord) and Freja/Frøj were linked with the cult’s rite, then it is possible that the carts discovered at Rappendam and Tranbær also resulted from fertility rites concerning pars-pro-toto cart sacrifices. In other words, the old fertility gods may have been worshipped from period II of the Pre-Roman Iron Age (like the Rappendam find) and onwards until the later part of the Early Roman Iron Age (like the Tranbær/Dejbjerg finds), when they were overcome and taken as hostages by the weapon-bearing Ases with Roman and Greek colleagues who were worshipped up into the Viking Age. Per Ole Schovsbo Næstved